Kinetics of Kaposi’s Sarcoma-Associated Herpesvirus Gene Expression - Sun, Ren (American Society for Microbiology, 1999)
Herpesvirus gene expression can be classified into four distinct kinetic stages: latent, immediate early, early, and late. Here we characterize the kinetic class of a group of 16 Kaposi’s sarcoma-associated herpesvirus (KSHV)/human herpesvirus 8 genes in a cultured primary effusion cell line and examine the expression of a subset of these genes in KS biopsies. Expression of two latent genes, LANA and vFLIP, was constitutive and was not induced by chemicals that induce the lytic cycle in primary effusion lymphoma (PEL) cell lines. An immediate-early gene, Rta (open reading frame 50 [ORF50]), was induced within 4 h of the addition of n-butyrate, and its 3.6-kb mRNA was resistant to inhibition by cycloheximide. Early genes, including K3 and K5 that are homologues of the “immediate-early” gene of bovine herpesvirus 4, K8 that is a positional homologue of Epstein-Barr virus BZLF1, vMIP II, vIL-6, and polyadenylated nuclear (PAN) RNA, appeared 8 to 13 h after chemical induction. A second group of early genes that were slightly delayed in their appearance included viral DHFR, thymidylate synthase, vMIP I, G protein-coupled receptor, K12, vBcl2, and a lytic transcript that overlapped LANA. The transcript of sVCA (ORF65), a late gene whose expression was abolished by Phosphonoacetic acid, an inhibitor of KSHV DNA replication, did not appear until 30 h after induction. Single-cell assays indicated that the induction of lytic cycle transcripts resulted from the recruitment of additional cells into the lytic cycle. In situ hybridization of KS biopsies showed that about 3% of spindle-shaped tumor cells expressed Rta, ORF K8, vIL-6, vMIP I, vBcl-2, PAN RNA, and sVCA. Our study shows that several KSHV-encoded homologues of cellular cytokines, chemokines, and antiapoptotic factors are expressed during the viral lytic cycle in PEL cell lines and in KS biopsies. The lytic cycle of KSHV, probably under the initial control of the KSHV/Rta gene, may directly contribute to tumor pathogenesis.